Strategi Pemasaran Katalog Produk (Studi Kasus Pengrajin Bambu Sukodono Sragen) - Aflit Nuryulia Praswati; Syamsudin Syamsudin; Muzakar Isa; Tulus Prijanto (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2016)
The promising prospect of bamboo industry is now evolving not only become handicrafts and small enterprises. Stakeholders of bamboo industry need to pay attention on the potency of this industry for its eco-friendliness, expediencies, and advantages. The bamboo industry in Sragen Regency for instance, develops properly but still faces marketing problems as its primary obstacle. Bamboo craftsmen are commonly supplying products based on customer orders. This study identifies the use of catalogue media to promote bamboo product in Sragen Regency. Using study case for descriptive qualitative, this research clarifies that bamboo craftsmen in Sragen Regency need support for development process. The catalogue arrangement process is started from identification of existing products, containing product name, size, usage, and price. Information of producer profile such as name, address, and telephone are equally important attributes for the catalogue. All information in the catalogue must represent profile and accessibility of the related product in order to attract consumers, and practically for its ease of marketing process. These long process, and bamboo handicraftsmen commitment in promotion obstruct this study to determine the efficency of the catalogue in raising bamboo market.